The Association of Dietary Diversity Scores and Breastfeeding with Weight, Length, and BMI in Jordanian Infants Aged 6 to 24 Months - Al-Bayyari, Nahla (Curr Dev Nutr, 2020)
OBJECTIVES: To assess how breastfeeding and dietary diversity relate to infant length-for-age Z-score (LAZ), weight-for-age Z-score (WAZ), and BMI-for-age Z-score (BMIz). METHODS: Nutrition-focused data were collected from infants (n = 149) ages 6 to 24 months from Maternal and Child Health centers in Northern Jordan. Breastfeeding, dietary, and anthropometric data were obtained from the Subjective Global Nutritional Assessment. As the WHO recommends infants breastfeed until 24 months, age-appropriate breastfeeding was defined as having eaten complimentary foods and breastfed the day prior. A dietary diversity score (DDS) was based on four food groups and was classified as adequate (having consumed grains, protein, and fruit or vegetable the day prior) or inadequate (lacking one of the aforementioned groups). RESULTS: Breastfed infants were more likely to have a lower WAZ, mean z-score of 0.16, than non-breastfed infants, mean z-score of 0.56 (P = 0.02). While differences between LAZ or BMIz were not statistically significant between breastfed and non-breastfed infants, mean BMIz was lower for breastfed infants 6 to 12 months compared to non-breastfed infants, mean z-score of 0.29 and 0.89 respectively (P = 0.03). Neither mean WAZ, LAZ, nor BMIz were significantly different in infants with adequate vs inadequate DDS. CONCLUSIONS: These results demonstrate the importance of breastfeeding in infants of all ages, but especially those from ages 6 to 12 months. Breastfeeding served as a protective factor for the WAZ and BMIz for infants, though more investigation should be done to identify if this transfers to infants ages 12 to 24 months as well. While the DDS provided qualitative information on infant diets, it did not confer a significant advantage in LAZ, WAZ, or BMIz. FUNDING SOURCES: This research received no specific grant from any funding agency, commercial, or not-for-profit sectors.